The Petrology of Granitoid Rocks of Kariya and environs, Bauchi Province, Northeastern, Nigeria - Ismail Kariya, Idris; Isah Haruna, Ahmed; Isa Jibrin , Abdulmajid; Abdulmumni, Yusuf; E.E. Ntekim; Abdulrauf , Rilwan; Yelwa Muhammed, Hamza; Mukhtar Hassan, Adamu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study area received less attention from earlier workers which they consider the rocks as older granites that were barren, but this study show the rocks are part of migmatite Complex and horst mineralized pegmatites. Detailed field mapping and sampling was conducted in order to identify and record the physical features of the rocks. Petrographic studies were also carried out to elucidate their mineralogy and structural features. Field investigations and petrographic studies reveal that the rocks in the study area are metamorphic rocks based on certain structures observed, some of the structures include ptygmatic folding, crenulation cleavage, pinch and swell, undulus extinction and pleochroic halo which are characteristics of metamorphic rocks. Therefore, the area was found to be underlained by migmatite rocks which were classified as banded orthogneiss, straumatic, and nebulitic migmatites and some intrusion of younger granites. Tin, tantalite, tourmaline, lithium and corundum mineralization were inferred.